Di Balik Peradangan: Tinjauan tentang Peran Antinosiseptif Sel Imun dalam Modulasi Nyeri - Raymond R. Tjandrawinata (PT Dexa Medica, 2025)
Immune cells have long been considered antagonists in pain physiology, as they have largely been viewed primarily through the lens of inflammation and nociceptive amplification. However, emerging research is reshaping this narrative. This article describes the evolving role of immune cells — not merely as proinflammatory molecules, but also as agents involved in pain modulation and suppression. Recent findings in neuroimmunology reveal a complex molecular dialogue between immune mediators and nociceptive pathways, particularly highlighting the contributions of regulatory T cells, macrophage subtypes, and glial cells in reducing nociceptive signals. Antinociceptive mechanisms mediated by cytokines, lipid-derived mediators, and immune-to neuronal communication are reviewed along with their translational potential in chronic pain therapy. By redefining the role of immune cells into central figures in the analgesic process, a paradigm shift is emerging, which requires an integrative approach in pain research and therapy.